Comparison of the response of microbial communities to region and rootstock disease differences in tobacco soils of southwestern China - Yi, Kai; Li, Zhenquan; Shang, Deshuang; Zhang, Chunguang; Li, Molun; Lin, Dengzheng; Wang, Shihai; Sun, Jianbin; Wang, Wei; Yang, Xiaoqian; Wang, Yiming (Frontiers in Microbiology, 2023)
Soil microorganisms are essential for crop growth and production as part of soil health. However, our current knowledge of microbial communities in tobacco soils and their impact factors is limited. In this study, we compared the characterization of bacterial and fungal communities in tobacco soils and their response to regional and rootstock disease differences. The results showed that the diversity and composition of bacterial and fungal communities responded more strongly to regional differences than to rootstock diseases, while bacterial niche breadth was more sensitive than fungi to regional differences. Similarly, the core bacterial and fungal taxa shared by the three regions accounted for 21.73% and 20.62% of all OTUs, respectively, which was much lower than that shared by RD and NRD in each region, ranging from 44.87% to 62.14%. Meanwhile, the differences in topological characteristics, connectivity, and stability of microbial networks in different regions also verified the high responsiveness of microbial communities to regions. However, rootstock diseases had a more direct effect on fungal communities than regional differences. This provided insight into the interactions between microbial communities, regional differences, and rootstock diseases, with important implications for maintaining soil health and improving tobacco yield and quality.